34. MEDICATION USE AND COST OF HEART FAILURE TREATMENT IN 2022: A STUDY AT A GRADE I HOSPITAL, HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Introduction: Heart failure represents a significant global public health concern, particularly among the elderly population. Furthermore, the economic burden associated with heart failure poses a substantial challenge to healthcare systems worldwide, including Vietnam.Objective: To analyze the economic burden of heart failure based on direct medical costs from a hospital perspective.Method: A retrospective analysis was conducted using electronic medical records of heart failure’ inpatients at Military Hospital 175 during 2022. Patients with heart failure as the primary diagnosis were included in the analytical dataset. The study estimated the cost burden based on healthcare services utilized within the hospital setting.Results: The study comprised 312 heart failure’ inpatients with a mean age of 67.1 ± 14.9 years. The total treatment cost for heart failure amounted to 7,199,653,394 VND, with the majority covered by health insurance. Pharmaceuticals, infusions, and medical supplies constitute the highest proportion of expenditures. Magnesium and potassium supplements represented the largest pharmaceutical expenditure at 75,408,753 VND (4.01% of total costs).Conclusion: The findings provide healthcare administrators with a comprehensive overview of heart failure-related expenditures, thereby facilitating the development of appropriate strategies for management and allocation of healthcare resources for heart failure treatment.
Keywords: cost of illness, direct medical costs, heart failure, inpatients.